Modern strategy of diagnostics and treatment of NSAID-induced enteropathy in elderly - Lipatova Т.Е.; Dudaeva N.G. (Саратовский научно-медицинский журнал, 2015)
The aim of the research is to improve the efficiency of diagnosis and treatment of NSAID-induced enteropathy at elderly patients with chronic pain (osteoarthritis, dorsopathy). Material and Methods. 300 elderly with osteoarthritis or dorsopathies regularly (8 weeks or more) receiving diclofenac at 75 mg per day were inspected. Clinical features, morphology, components of the diffuse endocrine system of the small intestine were studied. Results. It is defined, that at elderly patients with regular use of NSAIDs in 25% of cases postbulbar erosive duodenitis, in 75% of cases inflammatory and atrophic changes of the distal duodenum were diagnosed. Diagnosis of NSAID-induced enteropathy at elderly should include faecal calprotectin and morphology analysis of postbulbar area of the duodenum. Use meloxicam and sulfasalazine at older patients helps to eliminate or reduce intestinal dyspepsia, malabsorption, and intestinal inflammation on the results of faecal calprotectin and of histology of the small intestine. Conclusion. Elderly patients are at high-risk group for NSAID-induced enteropathy due to functional disturbances in the neuroendocrine system of the small intestine.